AGILE MANUFACTURING: SUMBER KEUNGGULAN BERSAING DI ERA GLOBAL - Alteza, Muniya - (Universitas Slamet Riyadi, 2005)
Abstract Competitive advantage now increasingly rests upon a dynamic capability to compete successfully in an environment of frequent, challenging and unpredictable change. Sustaining competitive advantage through price alone is no longer a viable strategy for most enterprises. They are now entering the era of agility and need to succeed in markets where a range of non-price advantages are expected by customers. This paper identifies the drivers of agility and discusses the portfolio of competitive advantage emerged from implementing agile manufacturing system. The agile manufacturing, a recently popularized concept, has been advocated as the 21st century manufacturing paradigm. In adopting and developing the key elements of agile manufacturing, there is a requirement for enterprises to overcome the philosophical challenges of a shift from mass/ lean production to the customization of agility. Besides that, enterprises should explore the key success factors to support successful agile implementation. Keywords: change, agility, manufacturing agile, requirement of customer.